Peran Indonesia dalam Meningkatkan Daya Saing Produk Kosmetik di Pasar Asean Melalui E-Commerce - Nurgiyanti, Tanti; Fithriya, Dwi Nur Laela (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2019)
Trade liberalization has been carried out through the ASEAN Economic Community (AEC). Barriers to trade both goods and services are no longer found. Through market trade liberalization, ASEAN countries are increasingly open to competition. E-Commerce trade is a trade that was born due to the development of information technology. Through trade E-Commerce creates opportunities and challenges for countries in Southeast Asia. One product that is widely traded is cosmetics. The cosmetics industry has a strategic opportunity to increase the income of Southeast Asian countries, especially Indonesia. Promising markets, abundant raw materials and the ability to absorb labor are quite a number of industries to be reckoned with. It is interesting to study further the existence of strata that sells cosmetic products both at home and abroad through E-Commerce trading continues to increase. But on the other hand local Indonesian cosmetic products are not able to compete with foreign products. As a result, losses can be experienced by cosmetic products SME entrepreneurs. This study is intended to determine the role of the Indonesian government in enhancing the competitiveness of cosmetic products in the Asean realm as well as regulations that regulate cosmetics trade through the use of e-commerce.